GENERAL CLINICAL CHARACTERISTICS OF SICK CHILDREN WITH PREMATURE VENTRICULAR AROUSAL (World Bulletin of Public Health, 2024)
The syndrome of premature ventricular arousal (CVV) of the heart means that part of the ventricular myocardium or the entire myocardium is activated by atrial (sinusoidal) impulses conducted along additional conductive pathways (DPP) before the impulses reach the ventricles through the normal conduction system of the heart. Manifestations of LVH are rare - from 0.15 to 3.1% of the general population, including 9% of the total number of children with cardiac arrhythmias. In childhood, the manifestation of this pathology is more common than in adulthood. This disease manifests itself in various forms – from constant clinical and electrophysiological manifestations in the manifest form to the absence of any subjective and objective symptoms in the latent form. The clinical significance of PVA is determined by the fact that almost 80.0% of patients sooner or later develop tachyarrhythmic attacks, both paroxysmal (i.e., transient) and chronic (permanently recurrent form) tachyarrhythmias, atrial fibrillation, atrial flutter, which when under certain conditions, they transform into atrial and ventricular fibrillation, which poses a threat to the patient’s life.
Keywords: Arrhythmia; children; pre-excitation of the ventricles